Texture dough machine / Muhammad Afiq Amsyar Mohamad Yusri and Ahmad Najmie Rusli - Mohamad Yusri, Muhammad Afiq Amsyar; Rusli, Ahmad Najmie (School of Mechanical Engineering, 2023)
Traditional dough kneading methods necessitate considerable energy expenditure and manual skill. In contrast, the introduction of a dough texture machine has revolutionized the process, enabling significant time and labor savings. The utilization of this machine demands precise adherence to operational protocols, ensuring consistent and predictable outcomes. Furthermore, this project encompasses the analysis and modification of existing dough texture machines to enhance their suitability for everyday use, aligning them with the specific needs and preferences of their intended user base. Notably, additional features have been incorporated into the design to expedite the dough-flattening process, reducing time and effort. In conclusion, this project strives to provide a practical solution to the challenges associated with dough preparation. By optimizing the functionality and convenience of dough texture machines, it endeavors to simplify the dough-making process for users, contributing to increased efficiency and quality in dough-based culinary endeavors.